2015
DOI: 10.1002/adom.201400528
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Alloy Quantum Dots: Toward Low‐Threshold Stimulated Emission and All‐Solution‐Processed Lasers in the Green Region

Abstract: Ultra‐low threshold stimulated emission is demonstrated upon both one‐ and two‐photon pumping from quaternary alloyed Cd(1−x)ZnxSe(1−y)Sy/ZnS quantum dots (QDs) in the green region for the first time. Moreover, an all‐solution‐processed whispering gallery mode laser is produced by coating Cd(1−x)ZnxSe(1−y)Sy/ZnS QDs on a self‐assembled hemisphere. These results represent a significant progress in green lasers and hold great potential in addressing the “green gap” challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…The ASE threshold of 2 μJ cm 2 (with 100 fs pulses, Figure 3 b) is one of the lowest values reported for solution-processed NC films. 14 , 38 41 …”
mentioning
confidence: 99%
“…The ASE threshold of 2 μJ cm 2 (with 100 fs pulses, Figure 3 b) is one of the lowest values reported for solution-processed NC films. 14 , 38 41 …”
mentioning
confidence: 99%
“…The four binary compounds made up by the four elements have different kinetic properties (see Scheme 1 a for K sp of four binary compounds), and the order of formation speeds of the four compounds (CdSe, CdS, ZnSe and ZnS) should be coincident with the sequence of radial distribution of the four compounds in the CdZnSeS QDs. Since the four compounds have similar chemical properties, well-defined interfaces between layers of different compounds are replaced by gradually varied alloy phases [ 21 , 22 , 23 ]. Scheme 1 b shows the core–shell structure of CdZnSeS QDs with the chemical composition gradient, which treats CdSe and CdS as core, ZnSe as middle shell and ZnS as outer shell.…”
Section: Resultsmentioning
confidence: 99%
“…The use of an alloyed compositiont op roduce NCs exhibiting opticalg ain was also adopted by Wang et al,w ho showed that quarternarya lloyedC d (1-x) Zn x Se (1-y) S y /ZnS core-shell NCs could exhibit ASE at green wavelengths with remarkably low thresholds of approximately 80 mJcm À2 . [31] In their approach, the core is kept large ( % 10 nm diameter) and the wavelengths of emission are varied by tuning the composition of the alloy. Given the large size of the core, the absorption cross-section is increased, quantumc onfinement is weak and Auger decay processes are inefficient compared with CdSe NCs emitting at the same wavelength.…”
Section: García-santamaría Et Al Demonstrated That Cdse Ncs Withmentioning
confidence: 99%